Classification of SMI Based QoS Attributes for Software as a Services - V, Balaji.; A, Manikandan.; A, Janakiram.; R, Vigneshwaran, (IJRDO -Journal of Computer Science Engineering, 2016)
Cloud computing is a model to produce thecomputing resources such as infrastructure, platform andsoftware over the internet in on-demand requirements. AsCloud computing creates huge opportunities and value inbusiness domains, the usage of cloud is creeping up dayby-day.Services models (IaaS, SaaS, PaaS) of the cloudcomputing is on fast mounting. In this paper, we havecompared and classified the key QoS attributes requiredfor software as a service based on Service MeasurementIndex framework.